Transneuronal retrograde degeneration of retinal ganglion cells and optic tract in hemianopic monkeys and humans. - Cowey, A; Alexander, I; Stoerig, P (2011)
Transneuronal retrograde degeneration of retinal ganglion cells after removal of primary visual cortex (area V1) is well established by quantitative neurohistological analysis of the ganglion cell layer in monkeys, but remains controversial in human patients. Therefore, we first histologically examined retinal degeneration in sectioned archived retinae of 26 macaque monkeys with unilateral V1 ablation and post-surgical survival times ranging from 3 months to 14.3 years. In addition, the cross-sectional area of the optic tract was measured in archived coronal histological sections of the brain of every hemianopic monkey and in sections from 10 control monkeys with non-visual bilateral cortical lesions. The ratios of nasal and temporal retinal ganglion cell counts in the contralesional eye and ipsi/contralateral optic tract areas were calculated and compared. They show that the decline was initially more pronounced for the optic tract, slackened after 3 years post-lesion and was steeper for the ganglion cells thereafter. Nevertheless, both measures were highly correlated. Second, we calculated ratios from structural magnetic resonance images to see whether the optic tracts of four human hemianopes would show similar evidence of transneuronal degeneration of their ipsilesional optic tract. The results were consistent with extensive and time-dependent degeneration of the retinal ganglion cell layer. The measures of the optic tracts provide evidence for comparable transneuronal retinal ganglion cell degeneration in both primate species and show that structural magnetic resonance image can both reveal and assess it.